Turbulence in the Individuation of Humankind: An "Enterview" with Murray Stein. (3rd April 2017) - Henderson, Rob
ABSTRACT: Murray Stein offers his Jungian view of the modern-day world of terrorism, believing it is part of a massive collision of cultural opposites striving toward the creation of a new global culture. He envisions the emergence of a third, which he terms "mundism, " out of the dialectic between tradition and modernity, and offers what he would do if he were a psychotherapist to the world. Remaining hopeful, he sees ultimately we are being directed to advanced states of consciousness.